2020
DOI: 10.1101/2020.05.25.20113043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Public Health Evaluation of Lockdown as a Non-pharmaceutical Intervention on COVID-19 Spread in India: National Trends Masking State Level Variations

Abstract: Introduction India has been under four phases of a national lockdown from March 25 to May 31 in response to the COVID-19 pandemic. Unmasking the state-wise variation in the effect of the nationwide lockdown on the progression of the pandemic could inform dynamic policy interventions towards containment and mitigation. Methods Using data on confirmed COVID-19 cases across 20 states that accounted for more than 99% of the cumulative case counts in India till May 31, 2020, we illustrate the masking of state-leve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…These stronger isolation policies were probably instrumental in flattening the curve of infections, though not sufficient to bring it to a complete halt. Similar to this case, strong lockdowns involving the enforcement of stringent restrictions to personal movements, use of public spaces, non-essential economic activities and in-office work have successfully contained the spread of COVID-19 in many countries and regions [28,[35][36][37][38][39][40]. Indeed, comparisons between related countries evidence that stricter lockdown policies reduce the number of COVID-19 deaths [41].…”
Section: Discussionmentioning
confidence: 94%
“…These stronger isolation policies were probably instrumental in flattening the curve of infections, though not sufficient to bring it to a complete halt. Similar to this case, strong lockdowns involving the enforcement of stringent restrictions to personal movements, use of public spaces, non-essential economic activities and in-office work have successfully contained the spread of COVID-19 in many countries and regions [28,[35][36][37][38][39][40]. Indeed, comparisons between related countries evidence that stricter lockdown policies reduce the number of COVID-19 deaths [41].…”
Section: Discussionmentioning
confidence: 94%
“…Even in Italy the CFR is reported more than the present study. 16 Studies [17][18][19][20] conducted in India are very few but they have also reported CFR more than the present study. Basu D et al 17 found CFR 3.5% in their study.…”
Section: Discussionmentioning
confidence: 49%
“…16 Studies [17][18][19][20] conducted in India are very few but they have also reported CFR more than the present study. Basu D et al 17 found CFR 3.5% in their study. Mazumder A et al 18 conducted a study on 1161 COVID patients and reported that 29 deaths and 94 patients recovered cases calculating CFR 2.5% and Recovery rate 8.1%.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations